Effects of tabata workout on immune cells response in physically inactive individuals - Noor, Nur Ain Syahira Mohd (2020)
High-intensity interval training (HIIT) is very popular nowadays as it produces similar positive results to moderate-intensity exercise, and at the same time, it is time efficient as it needs shorter exercise duration. To date, immune responses following HIIT is not well documented. Hence, the purpose of this study is to determine the effects of Tabata workout on immune cells responses among physically inactive individuals. A total of twelve physically inactive individuals (N = 12, 8 males and 4 females, age = 22.0 ± 0.9 years) from Health Campus Universiti Sains Malaysia participated in this one-arm experimental study. The Tabata workout programme was carried out 3 times per week for 6 weeks (a total of 18 sessions). During each exercise session, participants performed warming up, followed by 4 sets of Tabata workout and ended with cooling down. Each sets of Tabata workout contain 2 types of exercise (performed for 20 seconds) with rest intervals between exercises of 10 seconds. The rest interval between sets was 1 minute. Progressive load was employed in this study; the number of rounds for each sets of Tabata workout were increased from 2 rounds in the first 2 weeks of intervention to 3 rounds for the next 2 weeks of intervention and 4 rounds for the last 2 weeks of intervention. Heart rate (HR) and rate of perceived exertion (RPE) were recorded during each session. Participants’ body weight, body mass index (BMI), body fat percentage, and blood samples (2 mL) were measured at pre-, mid- and post-test. Blood samples were analysed for the total leukocytes, lymphocytes, neutrophils and monocytes count. One-way analysis of variance (ANOVA) with repeated measures was performed to measure significant difference between the three time points of measurement (at week 1, week 3 and week 6 of tests). The results showed that there were significant increases on total leukocytes (p = 0.042) and neutrophils (p = 0.039) following six weeks of Tabata workout. An increasing trend was also observed for monocytes count (p = 0.065) but not for the lymphocytes count (p = 0.304) following six weeks of Tabata workout. Participants’ body weight, BMI and body fat percentage were maintained throughout the intervention period. Thus, in conclusion, this study showed that chronic HIIT induced positive immune cells response among physically inactive individuals. Further studies are warranted for in depth understanding of the benefits of HIIT on immune response.